Systematic analysis of tensile properties of the TiVNbMoCr high entropy alloys in terms of the physical parameters - Zaidong Xu; Baolin Wu; Shihui Jiang; Naifu Zou; Yandong Liu; Claude Esling; Marie-Jeanne Philippe (Journal of Materials Research and Technology)
Optimizing elemental proportions is a potential pathway to enhance strength-ductility synergy of non-equimolar high entropy alloys (HEAs). This study designed a series of BCC-structured TiVNbMoCr alloys with different elemental proportions, and investigated the evolution of tensile properties. The effect of the independent parameters on tensile properties was systematically analyzed based on the experimental results. The independent parameters influencing the tensile properties were summarized as valence electron concentration (VEC), atomic radius mismatch δ, Burgers vector magnitude b (or lattice constant a), grain size d and geometric compatibility factor between grains m′. In comparison, VEC and δ play greater roles than b and d in strengthening the alloys. The tensile elongation of the alloys increases with decrease of a and VEC, and increase of m′ and d. With decreasing a, both yield strength and ductility could synergistically increase, which is significant for enhancing the strength-ductility synergy of TiVNbMoCr HEAs. The alloy with VEC of 4.69, δ of 4.526, b of 2.77 Å and d of 57 μm possesses the yield strength as high as 1303 MPa with an elongation of ∼6%.